IMPLEMENTASI PROJECT BASED LEARNING BERBASIS VIDEO DOKUMENTER SOSIAL DALAM MEMPERKUAT KARAKTER PEDULI SOSIAL SISWA SMP - Dea Kurnia Sari; Siti Ekowati Rusdini (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The low level of students’ social awareness, as reflected in limited empathy, low participation in social activities, and a tendency toward individualistic behavior, has become a challenge in social studies learning. This study aims to describe the implementation of Project-Based Learning (PjBL) using social documentary videos and to analyze its contribution to strengthening the social care character of Grade VIII C students at SMP Negeri 40 Semarang. The study employed a qualitative approach, with data collected through observations, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model and validated through source triangulation. The findings indicate that the implementation of PjBL based on social documentary videos enhanced students’ cooperation, responsibility, solidarity, and empathy toward social issues in their surrounding environment. Students also demonstrated more active engagement in the learning process as they gained contextual and collaborative learning experiences. Although several challenges were encountered, including limited instructional time, differences in students’ technical skills, and inadequate internet access, the learning activities remained effective in achieving the intended objectives. The findings suggest that the use of social documentary videos as project outcomes provides authentic learning experiences and serves as an innovative approach to strengthening students’ social care character in social studies education. Therefore, Project-Based Learning based on social documentary videos can be considered an effective alternative instructional strategy for fostering students’ social care character. ABSTRAK Rendahnya kepedulian sosial siswa yang ditunjukkan melalui kurangnya empati, partisipasi dalam kegiatan sosial, dan kecenderungan perilaku individualis menjadi tantangan dalam pembelajaran IPS di SMP. Penelitian ini bertujuan untuk mendeskripsikan implementasi Project Based Learning (PjBL) berbasis video dokumenter sosial serta menganalisis kontribusinya dalam memperkuat karakter peduli sosial siswa kelas VIII C di SMP Negeri 40 Semarang. Penelitian menggunakan pendekatan kualitatif dengan pengumpulan data melalui observasi, wawancara semi terstruktur, dan dokumentasi yang dianalisis menggunakan model interaktif Miles dan Huberman serta diuji melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa penerapan PjBL berbasis video dokumenter sosial mampu meningkatkan kerja sama, tanggung jawab, solidaritas, dan empati siswa terhadap permasalahan sosial di lingkungan sekitar. Siswa juga menunjukkan keterlibatan yang lebih aktif dalam proses pembelajaran karena memperoleh pengalaman belajar yang kontekstual dan kolaboratif. Meskipun terdapat kendala berupa keterbatasan waktu, variasi kemampuan teknis siswa, dan akses internet yang belum optimal, pelaksanaan pembelajaran tetap berjalan efektif dalam mencapai tujuan yang ditetapkan. Temuan ini menunjukkan bahwa pemanfaatan video dokumenter sosial sebagai produk proyek memberikan pengalaman belajar yang lebih autentik sekaligus menjadi inovasi dalam penguatan karakter peduli sosial pada pembelajaran IPS. Dengan demikian, Project Based Learning berbasis video dokumenter sosial dapat menjadi alternatif strategi pembelajaran yang efektif untuk mengembangkan karakter peduli sosial siswa.